Business communication a framework for success - O'Hair, Dan (South-Western College Pub., 2001)
Presenting a strategic approach to business communication, this text builds on a foundation of rhetorical and communication theories by including a range of real-company examples that make the theories come alive. These methods not only help to identify the many challenges encountered by today's business communicators, but also aim to foster a mastery of communication skills that should carry the reader well into his/her own career.